2010
DOI: 10.17221/259/2009-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Simplified PCR analysis of a mutation in the NHEJ1 gene causing collie eye anomaly in some dog breeds

Abstract: ABSTRACT:Collie eye anomaly (CEA) is an inherited eye disease affecting development of the choroids and sclera segregating in several, mostly herding breeds of dog. Phenotypic development of the disease varies greatly in the affected animals. Genetic control of its clinical variation is unknown so far. Affected dogs share a 7.8 kb deletion in intron 4 of the NHEJ1 gene. We report here population studies of 379 dogs (Australian Shepherd, Border Collie, Rough Collie, Smooth Collie, Shetland Sheep Dog, and Nova S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
8
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 12 publications
(14 reference statements)
7
8
3
Order By: Relevance
“…Almost all Shetland Sheepdogs tested in this survey had an intact NHEJ1 gene, and both NHEJ1 deletion patterns were detected in some individuals, with a frequency of 2.8%. This finding was extremely low compared to that described for the Czech Republic [13] and Denmark [19], where the mutation frequencies were 42.9% and 58.9%, respectively. Among the mutated cases examined in these investigations, the CEA/cea genotype was more frequent, except in Denmark, where the cea/cea genotype predominated [19].…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…Almost all Shetland Sheepdogs tested in this survey had an intact NHEJ1 gene, and both NHEJ1 deletion patterns were detected in some individuals, with a frequency of 2.8%. This finding was extremely low compared to that described for the Czech Republic [13] and Denmark [19], where the mutation frequencies were 42.9% and 58.9%, respectively. Among the mutated cases examined in these investigations, the CEA/cea genotype was more frequent, except in Denmark, where the cea/cea genotype predominated [19].…”
Section: Discussioncontrasting
confidence: 75%
“…Although NHEJ1 genotyping assay was available for CEA diagnosis, the geographic distribution of the NHEJ1 genotypic status across different countries remains undiscovered. In the Rough Collies, a remarkably high mutation frequency of 83.3% was observed in this study; this value is slightly higher compared to that reported in the Czech Republic, where the mutation frequency was 79.7% [13]. In Denmark, however, a considerably higher mutation frequency of 98.89% was reported [19].…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…The frequency of the CEA mutant allele is 0.244 (Dostal et al, 2010). To select against both mutations in a population of the breed requires a thoroughly defined breeding policy and consideration of what the population needs, instead of simply taking into account the desires of breeders.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the previous work mentioned, Dostal et al (2010) performed simplified analysis of the deletion without DNA isolation and Chang at al. (2010) utilised a rapid genotyping technique based on SYBR Green Real Time PCR which was applied to blood and saliva specimens on Flinders Technology Associated Filter Papers.…”
Section: Genetic Testingmentioning
confidence: 99%